Eventful Corporation / Suleyman Abdullah ... [et al.] - Abdullah, Suleyman; Mahali, Muhd. Haziq; Zolkiflee, Nur Afiqah; Japirin, Nazirah; Irwansyah, Nurezaty; Mohd. Saibi, Mohd. Anaffie (2015)
Our business name is Eventful.co. We creating a partnership form of business that organizing by 6 person of partners that each of them contributing a capital contribution and asset contribution. We provide a service that we call The Buzz. The Buzz is a service business that focusing on promoting an event through application form by an internet. This service is focusing on promoting event in all regions in Malaysia which consist of 13 states where by each region have their own specialty and differences according to their own social and business culture. The date of commencement of our business is on 1 June 2015 with our main location is at Putrajaya, Selangor. The reason of why we choose this place for set up our business premises is because Putrajaya is among one of many famous places in Malaysia. Putrajaya is where many Malaysian nor foreign people do business within this area as well as it serves as the federal administrative centre of Malaysia and Malaysia's commercial and financial centre. Besides, Putrajaya also surrounded by big companies The advantage that we see for doing this business is because this service is in line with the development of this country which is based on the Vision 2020. According to the vision, Malaysia want to achieve a developed nation status in economy, political, social, spiritual, psychological and cultural aspects such as that of the UK and Japan but with its own mould suitable with its culture and resources. Thus, our service is in line with the vision whereby we help to promote an agencies such as political, government nor private agencies event which can help them for getting more customers from various places as well as gain more profitability. Besides, our service also help the community more close to each other whereby a person can spend more time with their family and friends by selecting a place that near their house places or can planning for having a short or long vacation at a little bit far places from their house at the right day and at the right time. Next, our service becomes a platform that allows event organizers to plan, promote, and sell their event's tickets by using this application and we help by publish them across our Facebook, Twitter and other social-networking tools directly from the site's interface. Our service also enables attendees to find and purchase tickets to get these experiences. Although, our company generates revenue by charging organizers a fee of 3% of the ticket price plus RM1 per ticket sold, but does not charge any fee for free events.